INOVASI INKREMENTAL SEBAGAI STRATEGI & KEUNGGULAN DAYA SAING DI INDUSTRI FURNITURE VIETNAM (STUDI KASUS: FULL IN INDUSTRIAL, CO., LTD) - Susi Hartanto; Aditya Cipta Sugandha (Universitas Trisakti, 2019)
AbstractUS-China trading wars has brought positive impact to the growth of Vietnam furniture industry, due to supplier shifts or factory relocation. Many factories benefit with the increased number of purchase orders, but some suffer with stagnancy or even loss. Price, design, quality, finishing, and other factors all play significant roles in determining a factory’s performance. Full In as a research partner, have been running in only 1/3of the production capacity, consequently for its 20 percent higher price compared to competitors with similar products, and for too ordinary designs. Cheap is not always the best strategy. Design approaches (material replacement and appearance change) and strategies (reissue iconic furniture, develop American aesthetic preference furniture,develop refreshed contemporary furniture) are ways to mark Full In’s competitive advantage. Taking advantage of the trade momentum, and by collaboration with UPH research team, there are 8 new designs that will be exhibited in Vietnam International Furniture Fair 2020. In hope, good design may attract customers who afford higher prices; Full In has competitive advantage compared to other competitors.AbstrakAdanya perang dagang US-China memberikan dampak positif bagipertumbuhan industri furniture di Vietnam karena perpindahan supplier atau relokasi pabrik. Banyak pabrik mengalami peningkatan purchase order, tetapi ada juga yang stagnan atau justru menurun. Harga, desain, kualitas, finishing, dan faktor lainnya semua saling terkait menentukan performa sebuah pabrik. Full In sebagai mitra penelitian hanya mampu berjalan 1/3 dari kapasitas produksi seharusnya karena harga 20% lebih mahal dari kompetitor dengan produk serupa dan desain yang cenderung menduplikasi. Murah tidak selalu adalah strategi terbaik. Desain dengan pendekatan mengganti material dan penampilan; strategi merilis kembali produk ikon, mengembangkan produk dengan gaya Amerika dan sentuhan kontemporer merupakan strategi dan keunggulan desain yang diaplikasikan untuk Full In. Memanfaatkan momentum dagang dan lewat kolaborasi dengan tim peneliti UPH, ada 8 desain baru yang akan dipamerkan pada Vietnam International Furniture Fair premium, Full In memiliki keunggulan daya saing dibanding kompetitor lainnya.